Evaluasi Pembelajaran Jarak Jauh Dalam Jaringan Program Studi Pendidikan Bahasa Mandarin Universitas Negeri Jakarta - Andriani, Susi (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2023)
Online Distance Learning (online PJJ) at the Jakarta State University Mandarin Language Education Study Program (PSPBM UNJ) was initiated by "compulsion" due to the Covid-19 pandemic, but in its journey, online PJJ was seen as a program worth developing. Online PJJ is seen as an option to overcome space and time limitations. Therefore PSPBM UNJ intends to carry out activities for the Development of Chinese Language Online PJJ Models. This activity is the initiation of the Mandarin Language PJJ Daring Program development activity. In order to guarantee the quality of an activity or program, an evaluation activity is absolutely necessary. The word Evaluation comes from the English evaluation which contains the basic word value "value". The word value or value in evaluation terms is related to the belief that something is good or bad, right or wrong, strong or weak, sufficient or not enough, and so on. As the first stage of the Mandarin Language Online PJJ Model Development activity, in 2021 PSPBM UNJ has carried out evaluation activities on the implementation of online PJJ during the Covid-19 pandemic. This activity is carried out through student thesis research activities. Research activities are focused on evaluating the implementation of online PJJ linguistics courses which cover 4 language skills, namely listening, speaking, reading, and writing, as well as Mandarin knowledge courses, namely Grammar. Each study includes research on the conditions of student motivation, the obstacles faced by students, and online learning media used in learning activities. The results of this research are contained in fifteen thesis research reports of PSPBM UNJ students. This article discusses the overall results of this research.